Genetic modifiers of ambulation in the cooperative international Neuromuscular research group Duchenne natural history study. Issue 4 (13th March 2015) - Bello, Luca; Kesari, Akanchha; Gordish‐Dressman, Heather; Cnaan, Avital; Morgenroth, Lauren P.; Punetha, Jaya; Duong, Tina; Henricson, Erik K.; Pegoraro, Elena; McDonald, Craig M.; Hoffman, Eric P.; ,
Abstract : Objective: We studied the effects of LTBP4 and SPP1 polymorphisms on age at loss of ambulation (LoA) in a multiethnic Duchenne muscular dystrophy (DMD) cohort. Methods: We genotyped SPP1 rs28357094 and LTBP4 haplotype in 283 of 340 participants in the Cooperative International Neuromuscular Research Group Duchenne Natural History Study (CINRG‐DNHS). Median ages at LoA were compared by Kaplan–Meier analysis and log‐rank test. We controlled polymorphism analyses for concurrent effects of glucocorticoid corticosteroid (GC) treatment (time‐varying Cox regression) and for population stratification (multidimensional scaling of genome‐wide markers). Results: Hispanic and South Asian participants (n = 18, 41) lost ambulation 2.7 and 2 years earlier than Caucasian subjects ( p = 0.003, <0.001). The TG/GG genotype at SPP1 rs28357094 was associated to 1.2‐year‐earlier median LoA ( p = 0.048). This difference was greater (1.9 years, p = 0.038) in GC‐treated participants, whereas no difference was observed in untreated subjects. Cox regression confirmed a significant effect of SPP1 genotype in GC‐treated participants (hazard ratio = 1.61, p = 0.016). LTBP4 genotype showed a direction of association with age at LoA as previously reported, but it was not statistically significant. After controlling for population stratification, we confirmed a strong effect of LTBP4 genotype in Caucasians (2.4 years, p = 0.024). Median age at LoA with the protective LTBP4 genotype in this cohort was 15.0 years, 16.0 for those who were treated with GC. Interpretation: SPP1 rs28357094 acts as a pharmacodynamic biomarker of GC response, and LTBP4 haplotype modifies age at LoA in the CINRG‐DNHS cohort. Adjustment for GC treatment and population stratification appears crucial in assessing genetic modifiers in DMD. Ann Neurol 2015;77:684–696